Analysis of rheological properties and aging mechanism of bitumen after short-term and long-term aging. (1st March 2021) - Jiang, Wei; Bao, Rui; Lu, Hao; Yuan, Dongdong; Lu, Rong; Sha, Aimin; Shan, Jinhuan
Highlights: Influence of aging modes and aging times on virgin binders were compared. Effects of aging conditions on the rheological properties of binder were tested. Aging conditions impact on functional groups of bitumen were calculated. Effects of aging conditions on molecular weights of bitumen were obtained. Aging mechanism of bitumen was explored based on micro property tests. Abstract: Bitumen aging is one of the main causes of pavement performance deterioration. It is of great significance to clarify the impacts of different aging degrees on bitumen performance, molecular composition, and components for the laboratory simulation of bitumen aging and the analysis of the aging mechanism. For this purpose, in this study, two types of virgin bitumen were selected, and the rolling thin-film oven test (RTFOT) and the pressure aging vessel (PAV) methods were employed for testing according to the following designs: RTFOT (85–385 min, interval 60 min), PAV (10–30 h, interval 5 h), and RTFOT + PAV (85 min RTFOT + 10–30 h PAV, interval 5 h). Dynamic shear rheological (DSR) and bending beam rheological (BBR) tests were used to study the high- and low-temperature rheological properties of bitumen under different aging conditions. Based on Fourier-transfer infrared (FT-IR) spectroscopy, gel permeation chromatography (GPC), and rod thin-layer chromatography with flame ionization detection (TLC-FID) tests, the effects of different aging conditions on the functional groups, molecular weights, and components of bitumen were analyzed to explore the aging mechanism of bitumen. The result showed that compared with the RTFOT + PAV and RTFOT aging modes, PAV aging had a weaker influence on the bitumen rheological properties. The RTFOT aging method had a greater impact on the sulfoxide index ( SI ), aromatic index ( AI ), and long-chain index ( LCI ) but a lesser effect on the carbonyl index ( CI ); however, the PAV aging method had a significant impact on CI . The RTFOT + PAV aging method had the greatest influence on CI, SI, AI, and LCI . Moreover, for the RTFOT and PAV aging modes, after aging for a certain period, the proportions of the large-molecular-size (LMS), medium-molecular-size (MMS), and small-molecular-size (SMS) components tended to be stable. In the RTFOT + PAV aging mode, with prolonged aging time, there was no obvious stable trend in the proportion of the three components. Compared with the RTFOT and PAV aging modes, the RTFOT + PAV aging mode had a greater impact on the number of bitumen molecules. Under RTFOT and PAV, the aged bitumen exhibited a decrease in aromatics, an increase in resins and asphaltenes, and a basically unchanged proportion of saturates. Under the RTFOT + PAV aging mode, the aromatics decreased, the resins and asphaltenes increased, and the saturates decreased. For bitumen aging, when the long-term aging test conditions are limited, the RTFOT aging test can be used instead; for example, RP20 can substitute R385.